HUBUNGAN PERSEPSI PASIEN TENTANG MUTU ASUHAN KEPERAWATAN DENGAN KEPUASAN PASIEN DI RUANG PERAWATAN CANDI BARONG RSUD PRAMBANAN - Ahmad Zamzam Hariro; Sri Arini Winarti Rinawati; Deby Zulkarnain Rahadian Syah (Universitas Jenderal Achmad Yani Yogyakarta, 2015)
Background: Patients satisfaction is a major issue that should be payed attention on, in order to increase hospital quality. A hospital must provide the clients with their needs through excellent nursing care activities. Patients generally perceive the nursing care based on its tangible, reliability, responsiveness, assurance, and empathy. The patients’ perceptions towards nursing care quality will influence patients’ satisfaction. Objective: To investigate the relationship between patients’ perceptions of the nursing care with patients’ satisfaction. Methods: This research was observational analytic with cross-sectional design, used a purposive sampling technique. This study involved 40 samples. Data were collected with questionnaires, and were analyzed based on univariate and bivariate analyses. The bivariate analysis was Kendall's tau test with significance level of p <0.1. Results: Majority of respondents had good perception towards the nursing care quality (60%) and most respondents were satisfied with the nursing care (62.5%), Kendall's tau test resulted τ=0.476 with a p-value of 0.003 (p< 0.1). Conclusion: There was a significant relationship between the patients’ perception towards nursing care quality with the patients’ satisfaction in Candi Barong unit in Prambanan General Hospital. Keywords: Patients perception, nursing care quality, patients satisfaction